Dolphin, fox, hippo and ox : what Is a mammal? - Cleary, Brian P., 1959- (Animal groups are CAtegorical, 2013)
Clever rhymes from Brian P. Cleary and comical illustrations from Martin Goneau explain the traits that all mammals have in common and help you determine which creatures belong in this hairy group.